Consignas de livros didáticos de língua : uma análise dos atos de fala diretivos em português e em espanhol - Ferreira, Lizane (2007)
In the present research, it tries to investigate the question of the directives from a clipping centered in the analysis of didactic materials of Spanish and Portuguese of mother tongue language and foreign language, therefore, the focus of this work is how this didactic material -pupil interaction establishes. This dissertation aimes to carry through a descriptive-comparative study when analysing the act of directive speech - that it was called as consigns - in didactic books. In such a way, one becomes a reflexion on the functioning of the pedagogical speech in Portuguese language and Spanish language and searchs a definition for consigns from the analysis of its functioning in didactic books of education of languages. Aiming at the biggest precision of the results, it is verified how is done a formulation of consignses in didactic books, taking into consideration the type of language where the consigns are elaborated; the type of activities that follow them; the way and the oracional modality that the consigns can assume and the type of treatment found in them.The results demonstrate that, in general, consignses seem to have a behaviour that it more abides to the fact that are propagated in their mother tongue language or in foreign language that with the fact of being in Portuguese and Spanish. The consignses Portuguese and Spanish books of mother tongue language are similar, whereas of Portuguese and Spanish foreign language also. The only exception is the question of the treatment, that touches the matter of different varieties of one same language (Spanish of Argentina and Spaniard of Spain).